An Experimental Study on Multiscale Conductivity of Shale Fracturing. Issue 1 (1st December 2022) - Wang, Junchao; Wang, Lei; Li, Jiacheng; Ma, Haiyang; Ma, Mingwei; Chen, Chong
Abstract: Volumetric fracturing is an effective way to develop shale oil. Fracturing forms a complex system of fractures of various scales that can be divided into micro-fractures, secondary fractures, and primary fractures. To improve the conductivity of multiscale fractures in volumetric fracturing of Jimsar shale oil, conductivity experiments were performed under such conditions as rough fractures without proppant placement, rough fractures with proppant placement, and straight fractures with discontinuous sanding, thereby studying the change law of fracture conductivity at various scales. According to the results, micro-fracture conductivity is largely affected by the roughness of the fracture face; placing proppants can significantly increase the conductivity of rough fractures; the conductivity under the condition of discontinuous sanding is highly sensitive to stress; fractures with discontinuous sanding of an area of 40% show the best conductivity.